2017
DOI: 10.1103/physrevb.96.205201
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic excitons and their contributions to shift current transients in bulk GaAs

Abstract: Shift current transient are obtained for near band gap excitation of bulk GaAs by numerical solutions of the semiconductor Bloch equations in a basis obtained from a 14 band k·p model of the band structure. This approach provides a transparent description of the optically induced excitations in terms of interband, intersubband, and intraband excitations which enables a clear distinction between different contributions to the shift current transients and fully includes resonant as well as off-resonant processes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…As a strong THz field leads to a very rapid intraband acceleration through the entire Brillouin zone, we use in these simulations a k -independent interband dipole matrix element of eÅ, which is the average of 3 eÅ, the typical value often used for near-bandgap excitation of GaAs, and 1.5 eÅ, which is obtained for transitions at the upper band edge considering the scaling of the interband dipole matrix element. Therefore, this value is adequate and even slightly larger than the shift distance of GaAs, which amounts to approximately 2 Å at the fundamental bandgap 37 , 38 .…”
Section: Methodsmentioning
confidence: 91%
“…As a strong THz field leads to a very rapid intraband acceleration through the entire Brillouin zone, we use in these simulations a k -independent interband dipole matrix element of eÅ, which is the average of 3 eÅ, the typical value often used for near-bandgap excitation of GaAs, and 1.5 eÅ, which is obtained for transitions at the upper band edge considering the scaling of the interband dipole matrix element. Therefore, this value is adequate and even slightly larger than the shift distance of GaAs, which amounts to approximately 2 Å at the fundamental bandgap 37 , 38 .…”
Section: Methodsmentioning
confidence: 91%
“…The optoelectronic response is described by the quations of motion for the reduced density matrix elements ρ λλ ′ (k) = ⟨a + λ ′ k a λk ⟩, which are also known as the semiconductor Bloch equations [17][18][19][20]…”
Section: Theoretical Approachmentioning
confidence: 99%
“…Depending on the formation mechanism, photocurrents can be classified into different types: ballistic, shift, and rectification currents. These photocurrents have been investigated in bulk materials [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and quantum wells (QW) [15][16][17][18][19][20][21] but have not received much attention in one-dimensional (1D) systems such as quantum wires (QWR). Here, we present a theoretical study of the photocurrents in semiconductor QWRs.…”
Section: Introductionmentioning
confidence: 99%
“…Among several models to compute the electronic band structure, we choose to use the 14-band k • p model because it is able to describe the inversion asymmetry of GaAs and can be easily applied to semiconductor heterostructures. Using this approach, we recently obtained photocurrents including excitonic effects in bulk GaAs [11] and GaAs QWs [21]. It is shown that excitonic effects not only drastically change the existing shift current but also give ©2021 Vietnam Academy of Science and Technology rise to a ballistic current which is absent if the electron-hole attraction is not included.…”
Section: Introductionmentioning
confidence: 99%